Neat-en-ing up our understanding of p53 pathways in tumor suppression - Mello, Stephano Spano (Cell Cycle, 2018)
Although the p53 transcription factor has a well-established role in tumor suppression, little is known about how the non-coding targets of p53 mediate its tumor suppression function. Analysis of ncRNAs regulated by p53 revealed Neat1 as a direct p53 target gene. Neat1 has physiological roles in the development and differentiation of the mammary gland and corpus luteum, but its roles in cancer have been conflicting. To unequivocally understand Neat1 function in cancer, we used Neat1 null mice. Interestingly, we found that Neat1 deficiency promotes transformation both in oncogene-expressing fibroblasts and in a mouse model for pancreatic cancer. Specifically, Neat1 loss in the pancreas results in the enhanced development of preneoplastic lesions associated with dampened expression of differentiation genes. While the exact mechanisms underlying tumor suppression are unknown, there are several described mechanisms that may be responsible for Neat1-mediated tumor suppression. Collectively, these findings suggest that Neat1 enforces differentiation to suppress pancreatic cancer.